ALUR LAKON WAYANG KULIT SANG RAHWANA DALANG KI CAHYO KUNTADI - Prasetyo, Syamsul Gondo; Sulanjari, Bambang; Nuning, Zaidah (Universitas PGRI Semarang, 2021)
This study aims to describe the plot of the wayang kulit play Sang Rahwana the puppeteer Ki Cahyo Kuntadi. The type of this thesis research is descriptive qualitative. The source of the data comes from the video of the shadow puppet play Sang Rahwana the puppeteer Ki Cahyo Kuntadi. The data obtained are in the form of words, phrases, and sentences containing the plot of the wayang kulit story of Sang Rahwana the puppeteer Ki Cahyo Kuntadi. The data in this study were collected using the document technique, with the following stages: listening, transcript, and note-taking techniques. The data is then analyzed using an interactive model with the following stages: data reduction, data presentation, and concluding drawings.The results of the analysis in the text of the wayang kulit play Sang Rahwana the puppeteer Ki Cahyo Kuntadi is that the story in the wayang kulit has its own characteristics compared to other stories and this story has a straight or progressive type of plot.